Obesity : stigma, trends, and interventions. (Pediatric collections., 2018)
This collection of timely full text AAP articles explores the risks and interventions of pediatric obesity. Alarmingly, severe obesity appears to be increasing in prevalence faster than overweight or ""routine"" obesity and no single solution will end the Child Obesity epidemic. This article collection outlines the most successful and cost-effective approaches to this epidemic.